(untitled) (American Journal of Islam and Society, 2021)
Critical reflection on gender as a category of analysis within the study of Islam is a venture fraught with intellectual and cultural challenges. Despite tacit acceptance of the analytical significance of gender, the intersection of these two categories has made for a highly charged field of inquiry, polarizing Muslim and other audiences over its commitments, practices, and impact. The field is also gendered, with most of its scholars being women. This is characteristic of Women and Gender Studies at large and underlies its marginal epistemic and institutional status within various disciplines of the modern academy.[i] While this is also true for the study of Islam and Gender, other factors are also at play: Islam and Gender scholarship is increasingly conducted by women who are Muslim or of Muslim background. This has simultaneously mitigated and reproduced the modes of marginality associated with Women and Gender Studies.[ii] On the one hand, the postcolonial lens adopted in early Islam and Gender scholarship established the salience of this newly emerging field for deconstructing orientalist stereotypes of Muslim women. Leila Ahmed’s Women and Gender in Islam: Historical Roots of a Modern Debate (1993), Deniz Kendioyti’s Gendering the Middle East (1996), and Lila Abu-Lughod’s Remaking Women (1998) take full cognizance of Edward Said’s Orientalism (1978) in their critical investigation of essentializations of Islam which turn on gender. Studies recentring foundational texts as the ground for gender equality, like Qur’an and Woman (1992) by Amina Wadud, have provided postcolonial counter-readings in and of themselves. On the other hand, the growing number of Muslim women scholars engaged in the study of Islam and Gender has coincided with the global racialization of Muslim identity and rising Islamophobia since 9/11. This has led to their double penalization within their scholarly and religious communities. In the Western academy, their Muslim identity has been referenced to denigrate their scholarship as insiderist advocacy[iii]—or, in contrast, to celebrate it as a progressive niche of Islam. The reality, however, is closer to being “sequestered into a corner space,” as Julianne Hammer puts it.[iv]